(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article examines the issues of early detection of acute kidney injury in the acute phase of myocardial infarction, and a comparative analysis of NGAL, KIM-1 and cystatin C indicators is carried out. ROC analysis showed that NGAL (AUC=0.84, p<0.001) and KIM-1 (AUC=0.81, p<0.001) were 0.81, which was the second most significant change after NGAL. Cystatin C (AUC=0.81, p<0.001) was highly significant in acute kidney injury, but its sensitivity and specificity were low compared with NGAL.